Սարգոն II-ը և Արևելյան Փոքր Ասիայի երկրները - Քոսյան, Արամ («Զանգակ - 97»)
The paper deals with several aspects of Anatolian policy of Sargon П of Assyria (721-705 B.C.), which could further our knowledge of the main tendencies of the ethnopolitical development of this region. The author puts down a hypothesis, according to which, during the Anatolian cxpansion of Sargon II the roya) dynasties of two kingdoms - Bit-Burutash and Atuna (south-centrai Asia Minor) were representing an intrusive ethnic group, rather than local Luwian population. Assyrian kings had made use of this new ethnic element in their north-western policy against Luwian kingdoms of Tabal flate Tiglathpiieser III, Shalmaneser V and early Sargon П). But soon after Sargon II, s accesion, Bit-Burutash and Atuna started to show separatism which led to the weakening of Assyria, s positions in Tabal and whole eastem Asia Minor, culminating in 705 B.C. campaign against Gurdi of Kulumman. As a result, Assyria lost any control over territories to the north of Taurus ränge.
Keywords: Պատմություն